Prevalence of Stunting among Children under Five in Pediatric Hospital Al-Hasahisa, Al Jazirah State, Sudan - Alobid, Shaheeda Mohammed; Mustafa, Sara El kheir (International Journal of Child Health and Nutrition, 2024)
A cross-sectional descriptive design study was conducted in the pediatric hospital in Al-Hasahisa-Algazera state -Sudan, to ascertain the prevalence of stunting in children under five years old. There are 100 patients in the samples (46 girls and 54 males). The questionnaire used to collect the study’s primary data includes questions about participant content, sociodemographics, housing status, health, and nutrition. To estimate the patient’s percentage of stunting, anthropometric measures, including height/length for age and mid-upper arm circumference (MUAC), were also obtained. The data showed that most of the children were raised in nuclear homes. A significant correlation (P value <0.05) was seen between stunting and mother education. The parents’ educational attainment showed that a sizable percentage of fathers (52%) and mothers (45%) were illiterate. According to the findings, 82% of mothers were housewives, and 75% of fathers were employed. This finding demonstrated a significant (P value 0.004) relationship between income level and stunting, with weak income (22%), moderate-income (78%), and no income level. Furthermore, 36% of completed breastfeeders and 37% of non-completers showed a highly significant (P value 0.003) correlation between breastfeeding and stunting. During the course of the study, diarrheal diseases affected 68% of the children, while anemia (27%), malaria (52%), parasitic infections (17%), and chest infections (69%)were the most common conditions. 39% of the kids had severe malnutrition, and 18% had moderate malnutrition. The bulk of them, 78%, were stunted, with the remaining 19% mild, 11% moderate, and 48% severely stunted. According to the report, 35% of stunted children were female, and 43% of stunted children were male.